Prevalence and associated factors of active trachoma among children of 1 to 9 years in low-income countries of Africa: a systematic review and meta-analysis - Berhanu, Leykun; Berihun, Gete; Desye, Belay; Geto, Abebe Kassa; Daba, Chala (Frontiers in Public Health, 2025)
BackgroundActive trachoma is a form of infectious eye disease caused by Chlamydia trachomatis. An estimated 84 million individuals worldwide, primarily children, are affected by active trachoma. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence and predictors of active trachoma among children aged 1 to 9 years in low-income countries of Africa.MethodsRelevant literature was searched from electronic databases. The data was extracted using an Excel sheet and exported to STATA version 17 software. The levels of heterogeneity among studies were assessed using I2 and p-values. The findings were presented using a table, graph, and forest plot with a 95% confidence interval. A p-value of less than 0.05 was considered statistically significant.ResultAmong 2,665 studies searched, 25 were selected for meta-analysis. The pooled prevalence of active trachoma was 21.93% (95% CI; 16.67, 27.20). Presence of fly on child’s face (POR: 2.43: 95% CI; 1.63, 3.24), absence of waste disposal pit (POR: 2.10: 95% CI; 1.36, 2.84), living in rural areas (POR: 0.68: 95% CI; 0.43, 0.93), being female (POR: 1.57: 95% CI; 1.07, 2.07), presence of discharge on the child’s eye (POR: 3.03; 95% CI: 2.20, 3.86), absence of latrine (POR: 1.28: 95% CI; 1.05, 1.50), inadequate knowledge of trachoma (POR: 2.84: 95% CI; 1.69, 3.99), educational status of the child (POR: 0.51: 95% CI; 0.20, 0.81), water consumption (POR: 0.22: 95% CI; 0.04, 0.39), living with animals (POR: 3.35: 95% CI; 2.41, 4.29), latrine utilization (POR: 8.18: 95% CI; 2.16, 14.20), proper latrine utilization (POR: 2.85: 95% CI; 1.84, 3.86), and unclean child face (POR: 0.09: 95% CI; −0.00, 0.19) were the factors significantly associated with the pooled prevalence of active trachoma.ConclusionThe prevalence of active trachoma among children aged 1 to 9 years is high compared to the World Health Organization trachoma eradication plan. As a result, it is recommended to use latrines and incorporate trachoma awareness into school curricula and community outreach initiatives.